2017
DOI: 10.4103/2277-9175.209047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Effects of Resveratrol on Human Telomerase Reverse Transcriptase Messenger Ribonucleic Acid Transcript in Human Glioblastoma

Abstract: Background:Glioblastoma (GBM) is the most common and aggressive brain tumor, which has a poor prognosis despite the advent of different therapeutic strategies. There are numerous molecular biomarkers to contribute diagnosis, prognosis, and prediction of response to the current therapy in GBM. One of the most important markers that are potentially valuable is immortalization-specific or immortalization-associated marker named “hTERT messenger ribonucleic acid (mRNA)” the key subunit of telomerase enzyme, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…An opposite effect has been observed in different cancer cell lines where resveratrol reduces TERT and induces cellular apoptosis [ 176 , 177 ]. Resveratrol also inhibits the expression of TERT in metastatic glioblastom cancer cells, a phenomenon associated with dose-dependent prevention of cell proliferation and tumor regression [ 178 ]. Data on resveratrol-enhanced mitochondrial biogenesis through TERT are still limited, especially regarding neurodegenerative diseases.…”
Section: Mitochondrial Biogenesis Modulation By Resveratrol In Neurod...mentioning
confidence: 99%
“…An opposite effect has been observed in different cancer cell lines where resveratrol reduces TERT and induces cellular apoptosis [ 176 , 177 ]. Resveratrol also inhibits the expression of TERT in metastatic glioblastom cancer cells, a phenomenon associated with dose-dependent prevention of cell proliferation and tumor regression [ 178 ]. Data on resveratrol-enhanced mitochondrial biogenesis through TERT are still limited, especially regarding neurodegenerative diseases.…”
Section: Mitochondrial Biogenesis Modulation By Resveratrol In Neurod...mentioning
confidence: 99%
“…Among the stilbene compounds, trans-resveratrol, also known as 3,4,5,’-tri-hydroxystilbene, and pterostilbene (trans-3,5-dimethoxy-4-hydroxystilbene, which is a dimethylether analog of resveratrol), have been well-studied as promising dietary polyphenolic compounds with various chemopreventive and chemotherapeutic effects [134,140]. Previous studies indicated that the regulation of telomerase activity, telomere structure, and telomerase- and telomere-associated binding proteins have been suggested as new avenues for therapeutic intervention for some tumors in which it is difficult to induce apoptosis, such as glioblastoma (GBM) [140]. Mirzazadeh et al indicated that resveratrol (RSV) inhibited hTERT mRNA expression and cell proliferation in U-87 MG cells [140].…”
Section: Anticancer Effects Of Stilbene Compounds Are Mediated By mentioning
confidence: 99%
“…Previous studies indicated that the regulation of telomerase activity, telomere structure, and telomerase- and telomere-associated binding proteins have been suggested as new avenues for therapeutic intervention for some tumors in which it is difficult to induce apoptosis, such as glioblastoma (GBM) [140]. Mirzazadeh et al indicated that resveratrol (RSV) inhibited hTERT mRNA expression and cell proliferation in U-87 MG cells [140]. In a study by Kim et al, the stress hormone norepinephrine (NE) augmented cancer cell proliferation via the β2-adrenergic receptor and induced hTERT activity via Slug, which subsequently increased ovarian cancer cell invasion [143].…”
Section: Anticancer Effects Of Stilbene Compounds Are Mediated By mentioning
confidence: 99%
See 1 more Smart Citation